Determinants of Financial performance: a Study on selected cement companies in India - Dr. M. Nirmala,; K, Pavithra (The journal of contemporary issues in business and government, 2021)
This research was conducted to investigate the determinants of the financial performance selected cement companies in India. The performance of selected cement companies measured based on financial ratios like operating profit margin, gross profit margin, net profit margin, cash profit margin, return on capital employed, return on net worth, return on assets including revaluations, return on long term funds, current ratio, quick ratio, cash ratio, debt equity ratio, proprietary ratio, long term debt equity ratio, interest cover ratio and fixed asset to net worth ratio. The data for this research were collected from money control taken ten years data from 2009-2010 to 2018-2019. The findings are to be measured in path way analysis and the result showing the comparative financial performance of the selected ratios with dependent ratio Net Profit Margin.